Rancang Bangun Wastafel Otomatis Dengan Menggunakan Sensor Fotodioda - naila fauza (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2021)
Covid-19 is a virus that causes mild and dangerous respiratory tract infections. To predict the spread and increase in the number of infected people, people are advised to adopt a healthy lifestyle by washing their hands. Currently, the faucets used mainly in the sink system are manual faucets. To open or close the faucet, the user must touch the faucet directly. So we need an innovation in this sink system. The innovation made is in the form of an automatic faucet with a photodiode sensor where the use of this sensor can later help make hand washing activities easier and more practical. By placing your hands in a certain position, water and liquid soap will come out automatically. The method used is the experimental method. The procedure of this research includes designing, assembling, and testing tools. The results of the experiment showed that when the hand accesses the sensor in the sink, the sink water automatically comes out, and when the hand is released no water comes out, this indicates that a person no longer needs to turn the water faucet to turn on the water.